The impact of vaccination on transmission and death by COVID-19: an observational study in Portugal’s biggest primary care cluster (Journal of Statistics on Health Decision, 2022)
Vaccines are a key tool to manage the COVID-19 pandemic by preventing infection, hospitalization, severe disease, or death. In Portugal, information on vaccine effectiveness in real-life settings is still limited. Therefore, the main goal of this study is to evaluate the association between vaccination against COVID-19 and mortality and transmissibility in the population of the biggest Primary Care Cluster in Portugal, ACES Baixo Vouga (ACES BV).A retrospective, observational study including all reported cases of COVID-19 in ACES BV between December 2020 and September 2021 was conducted (N=18,415). Anonymized data on demographic, clinical, epidemiological characteristics and outcomes of interest of the COVID-19 confirmed cases were collected. To model vaccination’s association with death, a logistic regression analysis was performed. To estimate the effect of vaccination on the number of secondary cases, a zero-inflated negative binomial model was used.Of 18,415 confirmed cases included in this study, 1,981 (10.8%) were vaccinated. A complete vaccination scheme against COVID-19 (OR=0.22, CI95 0.09-0.47) and female sex (OR=0.42, CI95 0.30-0.57) protected against death, while age (OR=1.12, CI95 1.10-1.13), comorbidities (OR=4.14, CI95 2.27- 8.34) and the presence of symptoms (OR=1.72, CI95 2.27-8.34) increased the odds of death. A complete vaccination scheme (RR 0.63, CI95 0.49–0.81) decreased the risk for the number of secondary cases in the model without outliers.It is vital to monitor the vaccination effects in the real world and to better understand the characteristics of COVID-19 vaccine-induced immunity.
Keywords: COVID-19; Vaccination; Observational study; Mortality; Infectious Disease Transmission